Do personality traits matter? A comparative study of student preferences for teaching and learning activities and assessment modes in two different majors - Fjelkner, Annika Maria; Hakansson, Andreas; Rosander, Pia (Teaching and Learning Inquiry, 2019)
What, then, do we need to know about our students to better provide for more equitable outcomes? Who will succeed depend on many factors, and student personality traits is one factor less discussed in the engagement and First year experience literature. The aim of this study is to add to the teaching in higher education discussion by exploring how student differ regarding personality traits profile (IPIP-NEO-PI test; Goldberg, 1999), approaches to learning (R-SPQ-2F test; Biggs, Kember & Leung, 2001), and preference for teaching and learning activites and assessment modes. The on-line survey study was carried out in a small, teaching intensive Swedish university on students in a Business (n=144) and Pre-school teacher education program (n=179). Findings were that there seem to be systematic differences between the types of modes preferred, and also significant differences between the two majors regarding learning approach, motive and strategy. Findings are discussed in relation to Jarvis’ (2010) model of learning and disjuncture, Biesta’s (2005) discussion on educational relationships and risk, and Trowler’s (2008) concept of teaching and learning regimes (TLRs). There are two clear risks that teachers and curriculum developers face. First, teachers who are new or come from a different TLR may face the risk of alienating students and exposing them to extreme anxiety if using TLAs and assessment modes students are uncomfortable with and unused to. Second, teachers and curriculum developers run the risk of not challenging students enough, thus depriving them of valuable learning experiences.